(untitled) (Rajarshi Janak University Research Journal, 2025)
This study aims to evaluate the effectiveness of quick response (QR) codes on customer satisfaction. A standardized questionnaire was utilized in an online survey to collect data from 108 respondents. The purpose of the structured questionnaires was to gather demographic data on province, gender, age, occupation, and education. Additionally, it collected data on the ease of use, efficacy, monthly frequency of QR code usage, and user satisfaction. The simple process and helpful QR code research tool make it easy for customers to finish receiving and payment activities. The outcome of the reveals that while most Nepalese users are happy with the service, they only utilize it 10 to 20 times a month. According to the findings, consumers who were unsuccessful while using QR code services are utterly unhappy, but those who are used to using its services are highly content. The study also provides policymakers a basis for developing more effective QR code services, aimed at achieving an even higher satisfaction rate.